Virtual Nuclear Envelope Breakdown and Its Regulators in Fission Yeast Meiosis - Asakawa, Haruhiko; Yang, Hui-Ju; Hiraoka, Yasushi; Haraguchi, Tokuko (Frontiers in Cell and Developmental Biology, 2016)
Ran, a small GTPase, is required for the spindle formation and nuclear envelope (NE) formation. After NE breakdown (NEBD) during mitosis in metazoan cells, the Ran-GTP gradient across the NE is lost and Ran-GTP becomes concentrated around chromatin, thus affecting the stability of microtubules and promoting the assembly of spindle microtubules and segregation of chromosomes. Mitosis in which chromosomes are segregated subsequent to NEBD is called “open mitosis”. In contrast, many fungi undergo a process termed “closed mitosis” in which chromosome segregation and spindle formation occur without NEBD. Although the fission yeast Schizosaccharomyces pombe undergoes a closed mitosis, it exhibits a short period during meiosis (anaphase of the second meiosis; called “anaphase II”) when nuclear and cytoplasmic proteins are mixed in the presence of intact NE and nuclear pore complexes (NPC). This “virtual” nuclear envelope breakdown (vNEBD) involves changes in the localization of RanGAP1, an activator of Ran-GTP hydrolysis. Recently, Nup132, a component of the structural core Nup107-160 subcomplex of the NPC, has been shown to be involved in the maintenance of the nuclear cytoplasmic barrier in yeast meiosis. In this review, we highlight the possible roles of RanGAP1 and Nup132 in vNEBD and discuss the biological significance of vNEBD in S. pombe meiosis.